\left\{ \begin{array} { l } { \frac { 2 x - y } { 3 } = \frac { 3 x + y } { 2 } } \\ { x = 2 ( x + y + 1 ) } \end{array} \right.
Solve for x, y
x=2
y=-2
Graph
Share
Copied to clipboard
2\left(2x-y\right)=3\left(3x+y\right)
Consider the first equation. Multiply both sides of the equation by 6, the least common multiple of 3,2.
4x-2y=3\left(3x+y\right)
Use the distributive property to multiply 2 by 2x-y.
4x-2y=9x+3y
Use the distributive property to multiply 3 by 3x+y.
4x-2y-9x=3y
Subtract 9x from both sides.
-5x-2y=3y
Combine 4x and -9x to get -5x.
-5x-2y-3y=0
Subtract 3y from both sides.
-5x-5y=0
Combine -2y and -3y to get -5y.
x=2x+2y+2
Consider the second equation. Use the distributive property to multiply 2 by x+y+1.
x-2x=2y+2
Subtract 2x from both sides.
-x=2y+2
Combine x and -2x to get -x.
-x-2y=2
Subtract 2y from both sides.
-5x-5y=0,-x-2y=2
To solve a pair of equations using substitution, first solve one of the equations for one of the variables. Then substitute the result for that variable in the other equation.
-5x-5y=0
Choose one of the equations and solve it for x by isolating x on the left hand side of the equal sign.
-5x=5y
Add 5y to both sides of the equation.
x=-\frac{1}{5}\times 5y
Divide both sides by -5.
x=-y
Multiply -\frac{1}{5} times 5y.
-\left(-1\right)y-2y=2
Substitute -y for x in the other equation, -x-2y=2.
y-2y=2
Multiply -1 times -y.
-y=2
Add y to -2y.
y=-2
Divide both sides by -1.
x=-\left(-2\right)
Substitute -2 for y in x=-y. Because the resulting equation contains only one variable, you can solve for x directly.
x=2
Multiply -1 times -2.
x=2,y=-2
The system is now solved.
2\left(2x-y\right)=3\left(3x+y\right)
Consider the first equation. Multiply both sides of the equation by 6, the least common multiple of 3,2.
4x-2y=3\left(3x+y\right)
Use the distributive property to multiply 2 by 2x-y.
4x-2y=9x+3y
Use the distributive property to multiply 3 by 3x+y.
4x-2y-9x=3y
Subtract 9x from both sides.
-5x-2y=3y
Combine 4x and -9x to get -5x.
-5x-2y-3y=0
Subtract 3y from both sides.
-5x-5y=0
Combine -2y and -3y to get -5y.
x=2x+2y+2
Consider the second equation. Use the distributive property to multiply 2 by x+y+1.
x-2x=2y+2
Subtract 2x from both sides.
-x=2y+2
Combine x and -2x to get -x.
-x-2y=2
Subtract 2y from both sides.
-5x-5y=0,-x-2y=2
Put the equations in standard form and then use matrices to solve the system of equations.
\left(\begin{matrix}-5&-5\\-1&-2\end{matrix}\right)\left(\begin{matrix}x\\y\end{matrix}\right)=\left(\begin{matrix}0\\2\end{matrix}\right)
Write the equations in matrix form.
inverse(\left(\begin{matrix}-5&-5\\-1&-2\end{matrix}\right))\left(\begin{matrix}-5&-5\\-1&-2\end{matrix}\right)\left(\begin{matrix}x\\y\end{matrix}\right)=inverse(\left(\begin{matrix}-5&-5\\-1&-2\end{matrix}\right))\left(\begin{matrix}0\\2\end{matrix}\right)
Left multiply the equation by the inverse matrix of \left(\begin{matrix}-5&-5\\-1&-2\end{matrix}\right).
\left(\begin{matrix}1&0\\0&1\end{matrix}\right)\left(\begin{matrix}x\\y\end{matrix}\right)=inverse(\left(\begin{matrix}-5&-5\\-1&-2\end{matrix}\right))\left(\begin{matrix}0\\2\end{matrix}\right)
The product of a matrix and its inverse is the identity matrix.
\left(\begin{matrix}x\\y\end{matrix}\right)=inverse(\left(\begin{matrix}-5&-5\\-1&-2\end{matrix}\right))\left(\begin{matrix}0\\2\end{matrix}\right)
Multiply the matrices on the left hand side of the equal sign.
\left(\begin{matrix}x\\y\end{matrix}\right)=\left(\begin{matrix}-\frac{2}{-5\left(-2\right)-\left(-5\left(-1\right)\right)}&-\frac{-5}{-5\left(-2\right)-\left(-5\left(-1\right)\right)}\\-\frac{-1}{-5\left(-2\right)-\left(-5\left(-1\right)\right)}&-\frac{5}{-5\left(-2\right)-\left(-5\left(-1\right)\right)}\end{matrix}\right)\left(\begin{matrix}0\\2\end{matrix}\right)
For the 2\times 2 matrix \left(\begin{matrix}a&b\\c&d\end{matrix}\right), the inverse matrix is \left(\begin{matrix}\frac{d}{ad-bc}&\frac{-b}{ad-bc}\\\frac{-c}{ad-bc}&\frac{a}{ad-bc}\end{matrix}\right), so the matrix equation can be rewritten as a matrix multiplication problem.
\left(\begin{matrix}x\\y\end{matrix}\right)=\left(\begin{matrix}-\frac{2}{5}&1\\\frac{1}{5}&-1\end{matrix}\right)\left(\begin{matrix}0\\2\end{matrix}\right)
Do the arithmetic.
\left(\begin{matrix}x\\y\end{matrix}\right)=\left(\begin{matrix}2\\-2\end{matrix}\right)
Multiply the matrices.
x=2,y=-2
Extract the matrix elements x and y.
2\left(2x-y\right)=3\left(3x+y\right)
Consider the first equation. Multiply both sides of the equation by 6, the least common multiple of 3,2.
4x-2y=3\left(3x+y\right)
Use the distributive property to multiply 2 by 2x-y.
4x-2y=9x+3y
Use the distributive property to multiply 3 by 3x+y.
4x-2y-9x=3y
Subtract 9x from both sides.
-5x-2y=3y
Combine 4x and -9x to get -5x.
-5x-2y-3y=0
Subtract 3y from both sides.
-5x-5y=0
Combine -2y and -3y to get -5y.
x=2x+2y+2
Consider the second equation. Use the distributive property to multiply 2 by x+y+1.
x-2x=2y+2
Subtract 2x from both sides.
-x=2y+2
Combine x and -2x to get -x.
-x-2y=2
Subtract 2y from both sides.
-5x-5y=0,-x-2y=2
In order to solve by elimination, coefficients of one of the variables must be the same in both equations so that the variable will cancel out when one equation is subtracted from the other.
-\left(-5\right)x-\left(-5y\right)=0,-5\left(-1\right)x-5\left(-2\right)y=-5\times 2
To make -5x and -x equal, multiply all terms on each side of the first equation by -1 and all terms on each side of the second by -5.
5x+5y=0,5x+10y=-10
Simplify.
5x-5x+5y-10y=10
Subtract 5x+10y=-10 from 5x+5y=0 by subtracting like terms on each side of the equal sign.
5y-10y=10
Add 5x to -5x. Terms 5x and -5x cancel out, leaving an equation with only one variable that can be solved.
-5y=10
Add 5y to -10y.
y=-2
Divide both sides by -5.
-x-2\left(-2\right)=2
Substitute -2 for y in -x-2y=2. Because the resulting equation contains only one variable, you can solve for x directly.
-x+4=2
Multiply -2 times -2.
-x=-2
Subtract 4 from both sides of the equation.
x=2
Divide both sides by -1.
x=2,y=-2
The system is now solved.
Examples
Quadratic equation
{ x } ^ { 2 } - 4 x - 5 = 0
Trigonometry
4 \sin \theta \cos \theta = 2 \sin \theta
Linear equation
y = 3x + 4
Arithmetic
699 * 533
Matrix
\left[ \begin{array} { l l } { 2 } & { 3 } \\ { 5 } & { 4 } \end{array} \right] \left[ \begin{array} { l l l } { 2 } & { 0 } & { 3 } \\ { -1 } & { 1 } & { 5 } \end{array} \right]
Simultaneous equation
\left. \begin{cases} { 8x+2y = 46 } \\ { 7x+3y = 47 } \end{cases} \right.
Differentiation
\frac { d } { d x } \frac { ( 3 x ^ { 2 } - 2 ) } { ( x - 5 ) }
Integration
\int _ { 0 } ^ { 1 } x e ^ { - x ^ { 2 } } d x
Limits
\lim _{x \rightarrow-3} \frac{x^{2}-9}{x^{2}+2 x-3}